ANALISIS PROPORSI REMAJA DAN DEWASA USIA 15-24 TAHUN DENGAN KETERAMPILAN TEKNOLOGI INFORMASI DAN KOMPUTER DI INDONESIA PERIODE 2021-2023 - Deska Phanosthy Hutagalung; Euodia Marsa; Lodri Ariantoni; Jadiaman Parhusip (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
This study aims to analyze the proportion of adolescents and adults aged 15-24 years with information and computer technology (ICT) skills in Indonesia during the period 2021-2023. The data used comes from the official publication of the Central Statistics Agency (BPS) covering 38 provinces. The results show that the proportion of ICT skills nationally has increased, from 91.83% in 2021 to 94.31% in 2023. Provinces in the Java and Bali regions, such as DI Yogyakarta (98.95%) and Central Java (97.88%), have the highest proportion. In contrast, eastern regions of Indonesia, such as Papua (36.81%) and Maluku (82.80%), show lower proportions. Further analysis reveals that factors such as access to digital infrastructure, education levels and urbanization play an important role in influencing the disparity in ICT skills between regions. These disparities reflect inequalities in education equity and access to technology in Indonesia, which need to be addressed in policy formulation. Improved digital infrastructure, provision of community-based training, and collaboration between the government and private sector are recommended to support ICT skills development in areas with limited access. With these strategic efforts, it is expected that all Indonesian adolescents and young adults can have equal digital skills to support competitiveness and productivity.